Biological Effects of HIFU on HT-29 Colon Cancer Cell Lines - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
In this study, biological effects of High Intensity Focused Ultrasound (HIFU), which offer an effective treatment options for the treatment of solid tumors in recent years, will be determined on the colon cancer cell lines. © 2018 IEEE.
Keywords: apoptosis; cancer cell lines; cancer treatment; colon cancer; HIFU